1997
DOI: 10.5636/jgg.49.1165
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Spectroscopy of the A-X and B-X System of CH in Comet Austin (1990 V).

Abstract: We analyzed the A-X(0-0) band of CH, which appears in high-resolution spectra of comet Austin (1990 V), in order to understand fluorescence and collisional processes that influence the rotational structure of the A-X(0-0) band. Some of the weak lines of the A-X (0-0) band are clearly resolved, which have not been previously resolved with relatively low-resolution spectroscopy. We unambiguously confirmed the B-X (0-0) band lines around 3890 A, which had been suspected previously, but it had not been clearly ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…This agreement suggests that comets should be co-evolved from the same molecular cloud as other members of the solar system. Kim et al (1997) analyzed the high resolution spectra of the A-X band ('" 4300 A) and B-X band ("-J 3890 A) of CH of comet Austin (1990 V). They found that the CH bands do not achieve fluorescence equilibrium because its lifetime is too short ("-J 100 seconds) to equilibrate the quantum state populations of the bands.…”
Section: Optical Rangementioning
confidence: 99%
See 1 more Smart Citation
“…This agreement suggests that comets should be co-evolved from the same molecular cloud as other members of the solar system. Kim et al (1997) analyzed the high resolution spectra of the A-X band ('" 4300 A) and B-X band ("-J 3890 A) of CH of comet Austin (1990 V). They found that the CH bands do not achieve fluorescence equilibrium because its lifetime is too short ("-J 100 seconds) to equilibrate the quantum state populations of the bands.…”
Section: Optical Rangementioning
confidence: 99%
“…These fluorescence processes yield unique line emission of particular species, which have their own special structures of CH after 5 seconds exposure to sunlight with initial temperatures of 90 K and 0 K, respectively. Comparison with the observations of comet Austin shows that the nascent temperature of CH should be i"'.J 90 K. The Austin spectrum was obtained by Kim, Brown, & Spinrad (1997).…”
Section: Excitation and De-excitation Processes Of Cometary Moleculesmentioning
confidence: 99%